Designing an E-smart manufacturing readiness assessment tool for small and medium automotive businesses - Rahamaddulla, Syed Radzi; Sorooshian, Shahryar; Osman, Azim Azuan; Kamar, Ahmad Nazif Noor; Leman, Zulkiflle (Frontiers in Mechanical Engineering, 2025)
Manufacturing enterprises are currently facing radical challenges with the new concept of smart manufacturing. While most multinational enterprises have initiated their journey toward adopting smart manufacturing technologies, small and medium enterprises (SMEs) that are the mainstay of many manufacturing economies are still struggling to understand the complexities of smart manufacturing. Many of these enterprises are not ready to embrace the concept owing to the large initial investment required for technological advancement. Furthermore, failure to assess the readiness and current capabilities of the SMEs may obstruct achievement of their full potential in smart manufacturing. Therefore, the present study aims to explore essential criteria that must be included in the design of a readiness assessment tool for adopting smart manufacturing in automotive SMEs. Accordingly, we adopt a design and development research method along with the fuzzy Delphi technique to accomplish the research objectives. A self-administered questionnaire was then developed as an instrument to collect research data. A panel of 15 experts comprising government agency representatives, smart manufacturing practitioners, academic researchers, and SME consultants participated in the study. Data analysis revealed that the experts accepted all of the proposed criteria, as indicated by an expert consensus value exceeding 75%, a threshold value (d) ≤ 0.2, and a fuzzy score (A) ≥ the α-cut value of 0.5. These findings demonstrate that the suggested criteria have gained expert consensus and are necessary for designing and developing an E-smart manufacturing readiness assessment tool for automotive SMEs. Our research holds tremendous implications for small and medium automotive manufacturers intending to adopt smart manufacturing at their production facilities as well as policymakers designing further policies, aid, and future development strategies to enhance the business performances of SMEs.